PYCNODYSOSTOSIS; A RARE DISEASE CASE REPORT - Aziz, Farida; Fatima Farida,; Bashir, Neelam (Journal of Ayub Medical College Abbottabad, 2022)
Pycnodysostosis is a rare disease with very few reported cased all over the world. It was first described in 1963 by Maroteaux and Lamy. It is also known as Toulouse-Lautrec syndrome, after a French artist, Henri de Toulouse Lautrec. The affected gene, CTSK, was first isolated in 1996. It is an autosomal recessive osteochondrodysplasia, characterized by disrupted function of osteoclasts. Incidence of this disease is 1.7 per 1 million births with a male to female ratio of 1. 30% cases arise from consanguineous marriages.